Carex flava agg. (section Ceratocystis, Cyperaceae) in Poland: taxonomy, morphological variation, and soil conditions - Więcław, Helena (Biodiversity: Research and Conservation, 2015)
Sedges of Carex flava agg., typical of moist or wet habitats, are difficult to classify because of a lack of clear-cut morphological differences between them and the existence of numerous hybrids. This monograph presents results of research conducted in 2007-2012 in various parts of Poland. The plant material consisted of 1852 living specimens of Carex flava agg., collected from 80 localities, and dried specimens from 26 herbaria and from 7 private collections. The analysis involved 45 morphological characters (34 quantitative and 11 qualitative) and 9 soil parameters. Univariate, bivariate, and multivariate statistical methods were used to process the data. The results confirm the taxonomic classification dividing the C. flava group into 4 species: C. flava s.s., C. lepidocarpa, C. demissa, and C. viridula. This classification is based on (i) a high observed level of morphological separation of these taxa, resulting mostly from differences in generative characters, i.e. length of the utricle and its beak, and percentage ratio of beak length to total utricle length; (ii) integrity of the taxa at the sites where they coexist, although some intermediate forms resulting from hybridization are also present; (iii) habitat preferences of the taxa, especially the preference of C. lepidocarpa for calcareous sites and of C. demissa for slightly acidic soils. Thus in Poland the analysed taxa are morphologically well-defined and show clear ecological preferences. Continuous variation of morphological characters was observed among specimens of C. viridula, so it is not justifiable to distinguish its subspecies (sometimes classified even as separate species), described previously in literature. Consequently, the 2 subgroups of C. viridula were treated as local variants (i.e. varieties: var. viridula and var. pulchella), considering their different habitat requirements. Additionally, 5 hybrids were distinguished within C. flava agg.: C. ×alsatica [= C. demissa × C. flava], C. ×ruedtii [= C. flava × C. lepidocarpa], C. ×schatzii [= C. lepidocarpa × C. viridula], C. ×subviridula [= C. flava × C. viridula], and C. demissa × C. viridula; as well as 2 hybrids with C. hostiana as one of the parents: C. ×fulva [= C. demissa × C. hostiana] and C. ×leutzii [= C. hostiana × C. lepidocarpa].